Evaluation of different late left ventricular remodeling definitions for predicting long-term outcomes in acute myocardial infarction patients undergoing percutaneous coronary intervention. (14th October 2021) - Zhang, S; Xie, X; He, C; Lin, X; Luo, M; Lin, M; Fang, M; You, Z; Lin, K; Guo, Y
Abstract: Background: Late left ventricular remodeling (LLVR) after the index acute myocardial infarction (AMI) is a common complication, and is associated with poor outcome. However, the optimal definition of LLVR has been debated because of its different incidence and influence on prognosis. At present, there are limited data regarding the influence of different LLVR definitions on long-term outcomes in AMI patients undergoing percutaneous coronary intervention (PCI). Purpose: To explore the impact of different definitions of LLVR on long-term mortality, re-hospitalization or an urgent visit for heart failure, and identify which definition was more suitable for predicting long-term outcomes in AMI patients undergoing PCI. Methods: We prospectively observed 460 consenting first-time AMI patients undergoing PCI from January 2012 to December 2018. LLVR was defined as a ≥20% increase in left ventricular end-diastolic volume (LVEDV), or a >15% increase in left ventricular end-systolic volume (LVESV) from the initial presentation to the 3–12 months follow-up, or left ventricular ejection fraction (LVEF) <50% at follow up. These parameters of the cardiac structure and function were measuring through the thoracic echocardiography. The association of LLVR with long-term prognosis was investigated by Cox regression analysis. Results: The incidence rate of LLVR was 38.1% (n=171). The occurrence of LLVR according to LVESV, LVEDV and LVEF definition were 26.6% (n=117), 31.9% (n=142) and 11.5% (n=51), respectively. During a median follow-up of 2 years, after adjusting other potential risk factors, multivariable Cox regression analysis revealed LLVR of LVESV definition [hazard ratio (HR): 2.50, 95% confidence interval (CI): 1.19–5.22, P=0.015], LLVR of LVEF definition (HR: 16.46, 95% CI: 6.96–38.92, P<0.001) and LLVR of Mix definition (HR: 5.86, 95% CI: 2.45–14.04, P<0.001) were risk factors for long-term mortality, re-hospitalization or an urgent visit for heart failure. But only LLVR of LVEF definition was a risk predictor for long-term mortality (HR: 6.84, 95% CI: 1.98–23.65, P=0.002). Conclusions: LLVR defined by LVESV or LVEF may be more suitable for predicting long-term mortality, re-hospitalization or an urgent visit for heart failure in AMI patients undergoing PCI. However, only LLVR defined by LVEF could be used for predicting long-term mortality. FUNDunding Acknowledgement: Type of funding sources: None.